Germline structural variant as the cause of Lynch Syndrome in a family from Ecuador - Gemma Llargués-Sistac; Laia Bonjoch; Jenifer Muñoz; Xavier Domínguez-Rovira; Teresa Ocaña; Maria Isabel Alvarez-Mora; Celia Badenas; Anna Esteve-Codina; Carlos Reyes-Silva; Gabriela Jaramillo-Koupermann; Maria Teresa Rodrigo; Sandra López-Prades; et al. (npj Genomic Medicine)
Abstract Colorectal cancer (CRC) is one of the most common cancers worldwide. Lynch Syndrome (LS) is the most common form of hereditary CRC and it is caused by germline defects in the DNA-mismatch repair (MMR) pathway. It is of extreme importance for affected LS patients and their relatives to identify the germline causative alteration to provide intensified surveillance to those at risk and allow early diagnosis and cancer prevention. Current approaches for LS molecular diagnosis typically involve screening of the MMR genes by targeted gene-panel sequencing and rearrangement screening. We report the identification and characterization of a novel germline structural variant encompassing 48.757 kb, involving the 3’-ends of the MLH1 and LRRFIP2 genes, as the cause of LS in a family of Ecuador. Whole-genome sequencing and transcriptomics allowed the identification of the genomic rearrangement and highlights the importance of the use of these additional approaches to achieve a comprehensive molecular diagnosis in some LS patients.